Building blocks of an effective NGO. (1st July 2019) - Singhal, Rekha
Abstract : The purpose of this article is to identify dimensions and indicators of the effective management of non-governmental organisations (NGOs). In the study on which this article is based, through primary and secondary data analysis, 53 indicators of NGO effectiveness were identified and categorised into four dimensions: the operational system, the financial system, human resource management practices and the governance system. It was found that the operational system (13 indicators) contributed 27% towards NGO effectiveness, the financial system (10 indicators) contributed 26%, human resource management practices (15 indicators) contributed 24% and the governance system (15 indicators) contributed 23%. The findings are discussed in terms of a balance scorecard and the importance of governance in developing effective and sustainable NGOs. The study contributes to the theory on organisational effectiveness in the NGO sector and encourages NGOs' strategic planning and monitoring, and as well as the selection of appropriate NGOs for programme implementation.